EVALUASI MATURITAS MANEJEMEN LAYANAN SISTEM INFORMASI APLIKASI OVO MENGGUNAKAN FRAMEWORK ITIL VERSI 3 - Yuli Maharetta Arianti; Nani Mintarsih; Witari Aryunani (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
ABSTRAK OVO is one of the products from an Indonesian start-up that is engaged in the digital wallet. This application has obtained permission from Bank Indonesia to be designated as a money manager in digital form since August 2017 [1]. Some service models that can take advantage of OVO are buying and selling transactions, transfers between users and investment services, insurance, which can be done using a mobile device with Android or iOS OS. Evaluation of OVO performance on a regular basis needs to be done to determine the performance of OVO products. The evaluation is carried out using the ITIL Framework in assessing the quality of services in the OVO Information System Service Management, so that it can become analytical data that can be used in decision making in the future. Kata kunci: itil, dompet digital, mobile, ovo